1933 Haw. Sess. Laws 39-40 - (:unkn) unknown (My University, 1933)
An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, §§ 10-16: If a person committing a crime of violence or attempting to commit a crime of violence is armed unlawfully, that shall be treated as prima facie evidence of intent to commit said crime of violence. Firearms possessed contrary to the act shall be forfeited to the territory. Permits may be revoked under this act.
Keywords: CARRY - INTENT TO COMMIT CRIME